Influence of constipation on enuresis - María Rodríguez-Ruiz; Roberto Mendez-Gallart; Manuel García Mérida; Iván Somoza-Argibay (Elsevier, 2021)
Introduction: Constipation has classically been considered as a risk factor of enuresis, although there are increasingly more publications that report a similar prevalence of constipation in both enuretics and non-enuretics. Objective: To determine the influence of constipation in monosymptomatic and non-monosymptomatic enuresis, and to find out the prevalence of the three disorders, as well as the lower urinary tract dysfunction and bladder-bowel dysfunction in the population. Material and method: A cross-sectional observational prevalence study on a representative population sample of 5-9 year-old school boys and girls of Galicia, Spain. A questionnaire was completed in the schools on urinary and bowel habits, which included questions from the Paediatric Lower Urinary Tract Scoring System (PLUTSS) diagnostic questionnaire and grading of the lower urinary tract dysfunctions. The enuresis was diagnosed using the International Children's Continence Society (ICSS), and if it was also associated with diurnal symptoms, it was also classified as non-monosymptomatic enuresis. The constipation was evaluated using the Rome III criteria and the adapted Bristol stool scale. Results: A total of 772 questionnaires were included in the study. The prevalence of constipation was 20% and that of enuresis was 9.1% (62.9% monosymptomatic enuresis and 37.1% non-monosymptomatic), with the prevalence of bladder-bowel dysfunction being 5.2%. It was observed that constipation had no influence on the presence of monosymptomatic enuresis, but it did have an influence on non-monosymptomatic enuresis and lower urinary tract dysfunctions, where it was a significant risk factor. Conclusions: The differential diagnosis between monosymptomatic and non-monosymptomatic enuresis is essential in the initial evaluation of the patient with enuresis, since the therapeutic management and the characteristics of both disorders are different, with constipation only being a risk factor in cases of non-monosymptomatic enuresis. Resumen: Introducción: Clásicamente se ha considerado el estreñimiento como un factor de riesgo de la enuresis, aunque cada vez hay más publicaciones que reportan una prevalencia de estreñimiento similar en enuréticos y no enuréticos. Objetivo: Determinar la influencia del estreñimiento en la enuresis monosintomática y la no monosintomática y conocer la prevalencia de las 3 entidades así como de disfunciones del trato urinario inferior y disfunción vesicointestinal en la población. Material y método: Estudio observacional transversal de prevalencia sobre una muestra representativa de la población gallega de niños y niñas escolarizados de 5 a 9 años. Se realizó una encuesta en los colegios sobre hábitos miccionales e intestinales que incluía las preguntas del cuestionario Paediatric Lower Urinary Tract Scoring System (PLUTSS) de diagnóstico y graduación de las disfunciones del tracto urinario inferior. Se consideró la enuresis según los criterios de la Sociedad Internacional para la Continencia en Niños (ICSS), y si además asociaba sintomatología diurna, se clasificó como enuresis no monosintomática. El estreñimiento se valoró de acuerdo con los criterios Roma III y la escala de heces de Bristol adaptados. Resultados: Se incluyeron 772 encuestas en el estudio. La prevalencia de estreñimiento fue del 20%, la de enuresis del 9,1% (enuresis monosintomática 62,9% y no monosintomática 37,1%) y la de disfunción vesicointestinal del 5,2%. Observamos que el estreñimiento no influye en la presencia de enuresis monosintomática, pero sí en la enuresis no monosintomática y las disfunciones del trato urinario inferior, donde constituye un importante factor de riesgo. Conclusiones: Es fundamental el diagnóstico diferencial entre enuresis monosintomática y no monosintomática en la valoración inicial de un paciente enurético, ya que el manejo terapéutico y las características de ambas entidades son diferentes, constituyendo el estreñimiento un factor de riesgo solamente en el caso de las enuresis no monosintomáticas.